Predatory Journals - de Mira, Bianca Savegnago [UNESP] (Universidade Federal do Paraná, 2023)
Bianca Savegnago de Mira answers questions about predatory journals and its impact to the creation of scientific knowledge.
Periódicos Predatórios
Keywords: Journals; Predatory journals; Research ethics; Scientific production